OUTCOMES OF LABOR INDUCTION WITH DINOPROSTONE AT THE DEPARTMENT OF OBSTETRICS AND GYNECOLOGY, HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of labor induction using Dinoprostone at Hanoi Medical University Hospital and to identify associated factors.Materials and methods: A cross-sectional descriptive study was conducted on 84 pregnancies at ≥ 37 weeks of gestation with indications for labor induction and a Bishop score ≤ 5 points at the Department of Obstetrics and Gynecology, Hanoi Medical University Hospital, from January 2024 to February 2026.Results: The success rate of labor induction was 70.2%, and the rate of vaginal delivery was 44%. The incidence of uterine tachysystole was 8.3%, fetal distress 14.3%, and postpartum hemorrhage 3.6%. A Bishop score ≥ 3 was significantly associated with successful labor induction (OR = 5.8; 95% CI: 1.78-19.01; p = 0.004) and vaginal delivery (OR = 8.0; 95% CI: 2.37-27.25; p = 0.001).Conclusion: Dinoprostone is an effective method for labor induction with a high success rate and an acceptable safety profile in term pregnancies.
Keywords: Labor induction, Dinoprostone, Bishop score.